Bidirectional association between oral diseases caused by plaque and the inflammatory bowel disease: A systematic review and meta-analysis - Yuqing Zhang; Ce Bian; Chaoran Yu; Mengyao Zhu; Michael D. Weir; Hockin H.K. Xu; Yuxing Bai; Ning Zhang (Japanese Dental Science Review)
The bidirectional association between oral diseases caused by plaque and the inflammatory bowel disease remains unclear. Here, we comprehensively searched PubMed, EMBASE, Web of Science, and the Cochrane Library from inception to August 2024 to identify relevant studies. The relative risk (RR) from periodontal disease studies and the decayed, missing, and filled teeth (DMFT) index from caries-related studies was pooled, and calculating 95 % confidence intervals (CIs). Subgroup analysis, sensitivity analysis, and cumulative meta-analysis were employed to evaluate the robustness of the findings. The research adhered to PRISMA 2020 guidelines, incorporating 26 studies for systematic review and 20 for meta-analysis. The results indicated no significant increase in the overall risk of inflammatory bowel disease (IBD) in patients with periodontal disease (RR 1.31, 95 % CI 0.98–1.35); however, the risk of ulcerative colitis (UC) was higher compared to controls (RR 1.34, 95 % CI 1.04–1.73). Among IBD patients, the risk of periodontal disease was significantly elevated (RR 2.14, 95 % CI 1.62–2.81), as was the risk of dental caries (WMD = 2.51, 95 % CI 0.97–4.06). Additionally, UC patients exhibited a higher incidence of caries compared to Crohn’s disease (CD) patients (WMD = 3.97, 95 % CI 1.94–6.00). Sensitivity analyses and cumulative meta-analyses confirmed the stability of the results. In conclusion, IBD patients, particularly those with UC, should prioritize stringent oral hygiene to mitigate the risks of periodontal disease and dental caries. The association between periodontal disease and IBD warrants further investigation, and high-quality clinical studies are needed to provide more definitive and reliable evidence.